Study on self-medication among 2nd year medical students - Jagadeesh, K.; Chidananda, K. N.; Revankar, Sreenivas P.; Prasad, Nagaraja S. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Self-medication is use of medicines by individuals to treat self-recognized symptoms and illness. Self-medication is a common type of self-care behavior in the general public, but medical students differ in such practice, as they have knowledge about drugs and diseases. Methods: The present study involved 100 2nd year final term medical students in “Shivamogga Institute of Medical Sciences,” Shivamogga, Karnataka. Study was questionnaire based, and the results were analyzed by descriptive statistical methods. Results: In our study, 57% were female, and 43% were male. About 60% had knowledge about over the counter (OTC) drugs and considered Ayurveda drugs also OTC drugs. 25% considered self-medication entirely safe, whereas 61% considered self-medication have advantages. Self-medication was preferred by 72% as they felt that there is no need to consult health care professionals for a simple ailment. Self-medication was practiced by 62% students, among which 86% were appropriate, and 48% among them utilized knowledge from previous consultation. In 28% fever was the most common condition and paracetamol was the most commonly used drug. Conclusions: Self-medication was widely practiced among the students. They had good knowledge of OTC drugs. The practice of self-medication was almost appropriate. In general self-medication must be accompanied by appropriate information. Educating benefits and risks of self-medication is very much needed for medical students and the public now a day.